Salt concentrations in ice cores could unveil do events' recipe.
It is one thing to know that Earth has already faced abrupt climate changes-also known as Dansgaard-Oeschger (DO) events - in the past. But finding out the reasons for these dramatic and rather short term changes is another story, one that Dr. Rachael Rhodes from the University of Cambridge is reconstructing using chemistry records from ice cores taken from Greenland.